Presentation by Mayor Jane M. Tolmach to V.C. Community College District Board of Trustees Rough Draft - Jane Tolmach:::Mayor::: (1973)
A rough draft of a presentation urging the Ventura County Community College District Board of Trustees to approve the development of Oxnard Community College.